Phtoplankton community structure as a bioindicator of water quality in Carigara River Estuary, Leyte, Philippines - Superable, Lyka C.; Yap-Dejeto, Leni G. (2023)
Phytoplanktons are photosynthetic microorganisms considered to be bioindicators of water quality. At present, there is still insufficient data and no water quality assessments of Carigara's estuarine environments. Hence, a monthly collection of phytoplankton in the Carigara River Estuary was conducted from October 2022 to January 2023 to observe phytoplankton composition and assess its water quality. Sixty-four genera of phytoplankton were recorded. Bacillariophyta composed 63.7%, followed by Cyanophyta (23.5%), Chlorophyta (7.7%), Pyrrophyta (3.8%), Charophyta (0.9%), and Euglenophyta (0.4%). The top five most abundant genera based on their total mean density were Oscillatoria (4.9 x 10 raised to the power of 3 cells/L), Synedra (3.1 x 10 raised to the power of 3 cells/L), Skeletonema (1.9 x 10 raised to the power of 3 cells/L), Thalassionema (1.5 x 10 raised to the power of 3 cells/L), and Navicula (1.4 x 10 raised to the power of 3 cells/L). Diversity, richness, and evenness recorded were highest in the middle station, station 2 (H=2.8, Dmn=0.37, E=0.36), followed by the "freshwater" station 1 (H=2.58, Dmn=0.33, E=0.33), and finally, the "marine" station 3 (H=2.52, Dmn=0.27, E=0.29). The physico-chemical parameters that exhibited strong correlation to phytoplankton were light intensity, salinity, TSS, transparency, current velocity, pH, temperature, and nutrients. Finally, stations 1 and 2 had "moderate" water quality with both Integrated Phytoplankton Index (IPI) values of 0.58, but station 3 had a "low" quality rating with IPI value of 0.52, indicating emerging signs of declining water quality. Therefore, information on phytoplankton composition in estuarine environments is necessary for biodiversity management efforts.
Undergraduate thesis (B.S. in Biology) -- University of the Philippines, Tacloban.